Phytochemicals and antioxidants in watermelon (Citrullus lanatus) genotypes under hot arid region - CHOUDHARY, B R; HALDHAR, S M; MAHESHWARI, S K; BHARGAVA, R; SHARMA, S K (The Indian Journal of Agricultural Sciences, 2015)
Ten genotypes of red-fleshed watermelon [Citrullus lantus (Thunb.)] were estimated for various health promoting bioactive compounds. The evaluated genotypes showed wide variability in total phenols, total flavonoids, tannin, total carotenoids and lycopene contents. The antioxidant activity was estimated by using in vitro assay of cupric reducing antioxidant capacity (CUPRAC). The significant difference (P=0.05) was observed among evaluated watermelon genotypes for different phytochemicals and antioxidants. The total phenols varied from 16.77 to 21.41 mg/g, total flavoniods 55.60 to 100.93 mg/100g and tannin content 35.07 to 60.83 mg/100g on dry weight basis. Total carotenoids and lycopene ranged from 4.90 to 8.06 mg/100g and 3.74 to 6.80 mg/100g, respectively on fresh weight basis. The average antioxidant activity was found to be varied from 40.13 to 84.05 Î¼mol TE/100g fresh weight. The results indicate that red-fleshed genotypes of watermelon are good source of antioxidants and showed significant variability for different phytochemicals and antioxidants that could be exploited to develop new cultivars/hybrids of superior quality for nutritional security.